PERANCANGAN E-COMMERCE DI TOKO SAFA HOMEMADE BERBASIS ANDROID DENGAN MENGGUNAKAN MIT APP INVENTOR - Muhammad Prakarsa; Fanny Kusuma Hafiz (DAS Institute, 2022)
Technology is crucial for product/service providers to promote products/services to the public. Electronic commerce is the distribution, purchase, sale, and marketing of goods and services through electronic systems such as the internet, television, and other computer networks. In addition to product quality, the development of information technology systems also dramatically influences the public to be interested in the products offered. This study aims to develop android-based mobile commerce applied to the Safa Homemade Store. This mobile commerce application can make it easier for customers/buyers to order goods from stores anywhere and anytime via smartphones which have become the lifestyle of today's teenagers